كيمياء بيوعضوية - محلو, أحمد (Université of eloued جامعة الوادي, 2025)
الكيمياء البيوعضوية هي علم يجمع بين الكيمياء العضوية و الكيمياء الحيوية ، حيث تهتم بدراسة الظواهر البيولوجية من الناحية الكيميائية. و ترتكز الكيمياء البيوعضوية أساسا على دراسة المركبات الكيميائية العضوية التي لها دور في العمليات الحيوية أو البيولوجية. نظرا لأهمية هاته المادة لطلبة تخصص الكيمياء العضوية فمن الضروري توفير مرجع على شكل مطبوعة بيداغوجية يمكّنهم من التحضير و الفهم الجيّد لهذه المادة. هاته المطبوعة ت عنى أساسًا ببرنامج الكيمياء البيوعضوية المدرّسة في السنة الثالثة ليسانس كيمياء عضوية ، وهي مقسّمة إلى خمسة فصول شاملة لما هو مقرّر في هاته المادة. كما تحتوي هاته المطبوعة في جزء أخير على العديد من الأسئلة و التمارين النموذجية. .Bioorganic chemistry is a science that combines organic chemistry and biochemistry, as it is concerned with the study of biological phenomena from a chemical point of view. Bioorganic chemistry is mainly based on the study of organic chemical compounds that play a role in vital or biological processes. Given the importance of this subject for students of organic chemistry, it is important to provide a reference in the form of a pedagogical document that enables them to prepare and understand this subject. This document is mainly concerned with the bioorganic chemistry program taught in the third year of the Organic Chemistry specialty, and is divided into five chapters covering the program of this subject. This document also contains in a final part many typical questions and exercises.
Chimie Bio-organique
مطبوعة بيداغوجية موجهة لطلبة السنة الثالثة ليسانس كيمياء عضوية
Keywords: كيمياء بيوعضوية; الأحماض الأمينية; الببتيدات و البروتينات; الأحماض النووية; NATURAL SCIENCES::Chemistry::Organic chemistry::Bioorganic chemistry; amino acids; peptides; and proteins; glycosides (sugars); nucleic acids.